Eastern Mediterranean relief pottery in Istria - Starac, Alka (Rei Cretariae Romanae Fautorum Acta, 2024)
Eastern Mediterranean relief pottery of the Hellenistic period is represented in Istria by cup fragments of so-called Ionic and Megarian bowls, and Pergamene skyphoi. Eastern Mediterranean pottery decorated in relief became more popular in Istria during the Early Imperial period: lamps, table and ritual vessels like cups and paterae are represented. Dionysiac motifs are dominant in categories of lamps and tableware, represented mainly by Corinthian cups. Paterae and oinophoroi of Cnidian production are represented in much smaller numbers. An intensive import of relief tableware and lamps from Eastern Mediterranean sources began in the 2nd century AD and lasted throughout the 3rd century. Corinthian and Cnidian products dominated. Corinthian and Attic lamps (which are present in much smaller quantities) were broadly used daily for lighting and in funerary rituals. Cnidian lamps stand out with their variety of shapes, rich relief decoration, numerous wick-holes and dominant cultic and representative character.